Performance progression and variability of men`s 200 m individual medley at the 2022 FINA World Championships - Santos, C.; Costa, M. J. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
The aim of study was to compare performance progression and variability between entry times and all rounds in men's 200 m individual medley (200IM) at the 2022 FINA World Championships. Sixteen male swimmers who participated in the 200IM event at the 19th FINA World Championships were considered. Entry times (Et) and official race times for the heats (H), semi-finals (SF) and finals (F) were extracted from official websites and then converted from min to s. The Top16, semi-finalists (SFinalist), and finalists were considered. Repeated measures ANOVA followed by the Bonferroni post-hoc test was performed to analyse the round-to-round progression. Effect size (Partial Eta Squared, ES), the percentage of performance improvement (IMP, in %) and intra-swimmer's variation (%CV, in %) were also computed. A moderate and strong effect were found in Top16 and Finalist groups, respectively. A negative progression was found between Et-H for Top16 and Finalist, while a positive progression was observed between H-SF in the Finalist group. Thus, performance in the 200IM changed between rounds during the 2022 FINA World Championships. While the finalists race times got worse between Et-H, those improved between H-SF. SFinalist performance remained unchanged throughout all rounds. Thus, positive improvements between H-SF were crucial to achieve the final of the 200IM.